Effects of open-label placebos in clinical trials: a systematic review and meta-analysis - Melina von Wernsdorff (Nature Portfolio, 2021)
Abstract Open-label placebos (OLPs) are placebos without deception in the sense that patients know that they are receiving a placebo. The objective of our study is to systematically review and analyze the effect of OLPs in comparison to no treatment in clinical trials. A systematic literature search was carried out in February 2020. Randomized controlled trials of any medical condition or mental disorder comparing OLPs to no treatment were included. Data extraction and risk of bias rating were independently assessed. 1246 records were screened and thirteen studies were included into the systematic review. Eleven trials were eligible for meta-analysis. These trials assessed effects of OLPs on back pain, cancer-related fatigue, attention deficit hyperactivity disorder, allergic rhinitis, major depression, irritable bowel syndrome and menopausal hot flushes. Risk of bias was moderate among all studies. We found a significant overall effect (standardized mean difference = 0.72, 95% Cl 0.39–1.05, p < 0.0001, I 2 = 76%) of OLP. Thus, OLPs appear to be a promising treatment in different conditions but the respective research is in its infancy. More research is needed, especially with respect to different medical and mental disorders and instructions accompanying the OLP administration as well as the role of expectations and mindsets.